Chitosan coatings on lecithin stabilized emulsions inhibit mycotoxin production by Fusarium pathogens. (October 2018) - Wu, Dianhui; Wan, Jing; Lu, Jian; Wang, Xingguo; Zhong, Shaobin; Schwarz, Paul; Chen, Bingcan; Rao, Jiajia
Abstract: Mycotoxin deoxynivalenol (DON) is one of the most frequent contaminants in grains which poses a significant health risk to humans and livestock. As a potential food preservative with antifungal activities, the application of chitosan in food systems is currently limited because of the poor water solubility. To improve its solubility over a wider pH range, a series amounts (0.02–0.5 wt%) of chitosan with different molecular weight (low, medium, and high) were electrostatically deposited on lecithin stabilized medium chain triglyceride (MCT)-in-water emulsions at pH 3.0. Physically stable chitosan coated emulsions with the size of ∼0.4 μm at pH 5.0 were formed in the presence of 0.1 wt% chitosan concentration. Mycotoxin inhibition rates of chitosan coatings on emulsion droplets and chitosan solutions (0.1 wt%, pH 5.0) were measured in rice cultures colonized with Fusarium. graminearum isolates after 5 days of incubation. In general, mycotoxin inhibitory activities of chitosan coatings on emulsion droplets were better than that of chitosan solutions. Emulsions with 0.1 wt% high molecular weight chitosan and 0.1 wt% low molecular weight chitosan showed the highest activity in reducing the accumulation of 15ADON and 3ADON produced by F. graminearum isolate 124-1 and 125-1, respectively. Graphical abstract: Image Highlights: 0.1 wt% Chitosan was electrostatically deposited on lecithin stabilized emulsion droplets at pH 5. The mycotoxin inhibitory activity of chitosan was boosted by coating on emulsion droplets. The molecular weight of chitosan coating impact its inhibitory activity.